Perirenal Fat Volume Is Positively Associated With Serum Uric Acid Levels in Chinese Adults - Jiang, Ming; Li, Menghuan; Liu, Cuiying; Jing, Lei; Huang, Qiong; Wu, Tingting; Kong, Xiangqing; Liu, Jing (Frontiers in Endocrinology, 2022)
Background Visceral fat has been considered an important risk factor of elevated serum uric acid (SUA). Perirenal fat is a unique visceral fat around the kidneys that has special morphological and physiological features while its relationship with SUA remains incompletely elucidated. This study aimed to assess the association between perirenal fat volume (PrFV) and SUA. Methods A cross-sectional study was conducted in 102 subjects aged ≥ 18 years old recruited from Nanjing,China . The clinical characteristics including age, sex, drinking behavior, history of hypertension, body mass index, waist circumference, total cholesterol, fast plasma glucose, urea, serum creatinine, C-reactive protein, and SUA were recorded. PrFV was measured by ultrasonography. Multivariate linear models and the restricted cubic spline were used to investigate the association between PrFV and SUA. Results The median age of this study population was 52.5 (42.0-60.0) years and 56.9% were female. The median value of SUA was 5.73 mg/dL (4.58-6.80 mg/dL). The subjects were divided by PrFV tertiles and we found that the subjects in the highest PrFV tertile had a higher level of SUA compared to those in the lowest tertile (β=1.86, 95%CI 1.23–2.48, P for trend <0.001).The positive association also remained after adjustment for potential covariates (tertile3 versus tertile1: β=0.99, 95%CI 0.35-1.63, P for trend =0.005). There was an increase of approximately 0.53 mg / dL in SUA per 1-fold increase in PrFV (β=0.53, 95%CI 0.02-1.04, P for nonlinearity = 0.637). Conclusion Our results confirmed a positive independent relationship between PrFV and SUA in Chinese adults. This study suggested that perirenal fat might constitute a potential risk factor for elevated serum uric acid levels.